2022
DOI: 10.1002/2211-5463.13416
|View full text |Cite
|
Sign up to set email alerts
|

Influenza antivirals and animal models

Abstract: Influenza A and B viruses are among the most prominent human respiratory pathogens. About 3–5 million severe cases of influenza are associated with 300 000–650 000 deaths per year globally. Antivirals effective at reducing morbidity and mortality are part of the first line of defense against influenza. FDA‐approved antiviral drugs currently include adamantanes (rimantadine and amantadine), neuraminidase inhibitors (NAI; peramivir, zanamivir, and oseltamivir), and the PA endonuclease inhibitor (baloxavir). Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 178 publications
(229 reference statements)
0
17
0
Order By: Relevance
“…The ability of neuraminidase/sialidase inhibitors siastatin B (Kudo et al, 1993; Tailford et al, 2015), N‐acetyl‐2,3‐dehydro‐2‐deoxyneuraminic acid (Magesh et al, 2008), Fv32r (previously also synthesized as 4‐amino‐DANA (Smith et al, 2001)), and the zanamivir precursor zanamivir amine (Caceres et al, 2022) to inhibit Cj0843c suggests that such inhibitors could be starting points for design of more‐potent LT inhibitors. Zanamivir is FDA‐approved to treat flu, and many sialidase inhibitor analogs have previously been synthesized (Keil et al, 2022; Laborda et al, 2016), which could be tested for their ability to inhibit LTs.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of neuraminidase/sialidase inhibitors siastatin B (Kudo et al, 1993; Tailford et al, 2015), N‐acetyl‐2,3‐dehydro‐2‐deoxyneuraminic acid (Magesh et al, 2008), Fv32r (previously also synthesized as 4‐amino‐DANA (Smith et al, 2001)), and the zanamivir precursor zanamivir amine (Caceres et al, 2022) to inhibit Cj0843c suggests that such inhibitors could be starting points for design of more‐potent LT inhibitors. Zanamivir is FDA‐approved to treat flu, and many sialidase inhibitor analogs have previously been synthesized (Keil et al, 2022; Laborda et al, 2016), which could be tested for their ability to inhibit LTs.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of delivering cells primed for viral resistance to infected airways has therapeutic potential beyond CF. Globally, severe viral infection represents a major health burden with ~60,000 deaths per year caused by respiratory syncytial virus (RSV) (51), 300,000-650,000 deaths per year caused by influenza-A and-B (52), and ~15 million deaths in two years since the emergence of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in 2019 (53). Unlike cell therapy for CF where cell engraftment is key, the primary goal of cell therapy for severe viral infection would be to promote lung repair.…”
Section: Discussionmentioning
confidence: 99%
“…In the second review, Pablo A. González and co‐authors explored the role of HSF1 in viral infections, and whether positive or negative modulation of this protein may have potential for the treatment of viral infections [ 7 ]. Recent years have reminded all of us of the importance of the continued development of effective antiviral agents, and C. Joaquin Caceres, Daniel R. Perez, and co‐authors provided a timely summary of the approved influenza antivirals, antiviral strategies under evaluation in clinical trials, and preclinical evaluations of novel compounds effective against influenza in animal models [ 8 ]. Understanding the host's own immune response to viral infection is also key to prevention and treatment, and Andrea Cimarelli and co‐authors concluded the issue by discussing the mechanisms by which ISG20 inhibits a broad spectrum of viruses [ 9 ].…”
Section: New Developments In 2022mentioning
confidence: 99%